2014
DOI: 10.1371/journal.pone.0093733
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation Drives the Positive Effects of Plant Richness on Trace Metal Removal in a Biodiversity Experiment

Abstract: BackgroundPhytoextraction is an environmentally acceptable and inexpensive technique for mine tailing rehabilitation that uses metallophyte plants. These plants reduce the soil trace metal contents to environmentally acceptable levels by accumulating trace metals. Recently, whether more trace metals can be removed by species-rich communities of these plants received great attention, as species richness has been reported having positive effects on ecosystem functions. However, how the species richness affects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…This is important because many of the ecosystem services provided by plants may in fact be more related to root structural traits than simple root biomass. For example, in a study investigating effects of plant species richness on metals removal in soils affected by mine tailings, Wang et al ( 2014 ) found that the functional diversity metrics using community-weighted mean trait values of root length were related to the amount of Cu, Cd, and Zn incorporated into plant tissue. Thus a sole focus on root biomass may miss important biodiversity effects on root traits, which can strongly affect ecosystem processes independently of root biomass.…”
mentioning
confidence: 99%
“…This is important because many of the ecosystem services provided by plants may in fact be more related to root structural traits than simple root biomass. For example, in a study investigating effects of plant species richness on metals removal in soils affected by mine tailings, Wang et al ( 2014 ) found that the functional diversity metrics using community-weighted mean trait values of root length were related to the amount of Cu, Cd, and Zn incorporated into plant tissue. Thus a sole focus on root biomass may miss important biodiversity effects on root traits, which can strongly affect ecosystem processes independently of root biomass.…”
mentioning
confidence: 99%
“…Facilitation is a positive interaction in assembling ecological communities and is recognized as an important conditional factor for the success of phytoremediation strategies (Fre´rot et al 2006;Brooker et al 2008;Parraga-Aguado et al 2013;Wang et al 2014). It occurs when a plant species, referred to as a nurse plant, facilitates the establishment of other species by locally changing biotic and/or abiotic conditions, such as light and nutrient availability (Brooker et al 2008;Soliveres et al 2010;Bonanomi et al 2011;Beltra´n et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It occurs when a plant species, referred to as a nurse plant, facilitates the establishment of other species by locally changing biotic and/or abiotic conditions, such as light and nutrient availability (Brooker et al 2008;Soliveres et al 2010;Bonanomi et al 2011;Beltra´n et al 2012). The identification of nurse plants is important to improve germination, growth, and survival of a diversity of plant species in heavy metal-polluted environments (Fre´rot et al 2006;Padilla and Pugnaire 2006;Parraga-Aguado et al 2013;Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the numerical values of the indices are used in more involved calculations, such as relating them with other types of ecosystem properties (Wang et al . ), using them to estimate the relevance of indirect interactions (Michalet et al . ), to compare beneficiary effects with the feedback effect of the target species on its benefactor (Schöb et al .…”
Section: Introductionmentioning
confidence: 99%